Get rooted : reclaim your soul, serenity, and sisterhood through the healing medicine of the grandmothers - Moreno, Robyn, 1973- (Hachette Go, an imprint of Hachette Books, 2023)
Follows Robyn Moreno as she sets out on a journey of personal growth to discover her true self with the help of wisdom from friends and family and traditions passed down by her ancestors.